2015
DOI: 10.1136/gutjnl-2014-306842
|View full text |Cite|
|
Sign up to set email alerts
|

Pathobiology of liver fibrosis: a translational success story

Abstract: Reversibility of hepatic fibrosis and cirrhosis following antiviral therapy for hepatitis B or C has advanced the prospect of developing antifibrotic therapies for patients with chronic liver diseases, especially non-alcoholic steatohepatitis. Mechanisms of fibrosis have focused on hepatic stellate cells, which become fibrogenic myofibroblasts during injury through ‘activation’, and are at the nexus of efforts to define novel drug targets. Recent studies have clarified pathways of stellate cell gene regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
695
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 784 publications
(740 citation statements)
references
References 136 publications
7
695
0
11
Order By: Relevance
“…Fibrosis is a pathological state similar to an aberrant scarring process; it is characterized by the abnormal accumulation of extracellular matrix (ECM) components as a consequence of a chronic inflammatory response [118,119]. It is well known that myofibroblast (MFB) is the main cell type with the capacity to synthesize collagen in the fibrotic state [119,120].…”
Section: Purinergic Signaling Emt and Fibrosismentioning
confidence: 99%
“…Fibrosis is a pathological state similar to an aberrant scarring process; it is characterized by the abnormal accumulation of extracellular matrix (ECM) components as a consequence of a chronic inflammatory response [118,119]. It is well known that myofibroblast (MFB) is the main cell type with the capacity to synthesize collagen in the fibrotic state [119,120].…”
Section: Purinergic Signaling Emt and Fibrosismentioning
confidence: 99%
“…6e8 There is optimism that these various approaches will result in the development of effective antifibrotic therapies even when the underlying primary disease persists. 5 Many studies have found that alterations in HSC activation are orchestrated by dynamic changes in the expression and/or action of a host of soluble or cell-associated signaling molecules, 6,9 but an additional mechanism of HSC regulation has recently come to light with our finding that fibrogenic pathways in HSCs are modulated by exosomes. 10 Exosomes, produced by most if not all cells of the body, are nanosized membranous vesicles that are capable of delivering complex molecular payloads to recipient cells, which may become functionally reprogrammed according to the molecular cues received.…”
mentioning
confidence: 99%
“…This excessive deposition of ECM proteins at sites of tissue damage, resulting from, for example, viral infection or alcoholic liver disease, is a consequence of a dysregulated wound‐healing response. Although reversible if the source of the injury is eliminated, unchecked liver fibrosis can develop into cirrhosis and even liver failure due to portal hypertension, with the only treatment option being transplantation 1, 2. Chronic liver disease is a major cause of mortality worldwide and correlates with an increased risk of hepatocellular carcinoma 3…”
Section: Introductionmentioning
confidence: 99%